Incognito. - Le Bas, Jessica (Auckland University Press, 2007)
This engaging collection of poetry, split into six sections and written in an intimate and affectionate tone, is wonderfully diverse. The lyrical poems address issues that run the gamut from family, friends, and domestic situations; to children's perception of the world; the seashore; and political situations based on the author's experience as a United Nations worker in the former Yugoslavia. Winner, NZSA Jessie Mackay Award for Best First Book of Poetry 2008.